Solvothermal synthesis and effects of Fe-doping on KTa0.63Nb0.37O3 nanocrystallines. Issue 10 (2nd October 2020) - Yu, Hua-Jian; Hu, Yan-Yan; Zhang, Fei; Yang, Cheng-Kai; Zhang, Hua-Di; Li, Jing; Zhang, Yuan-Yuan; Wang, Xu-Ping; Liu, Bing; Wei, Lei
Abstract: KTa0.63 Nb0.37 O3 (KTN) and Fe doped KTa0.63 Nb0.37 O3 particles have been synthesized by the mixed solvothermal method at 200 °C for 24 h. The influence of Fe-doping on the phase structure and micro-morphology of KTN was investigated by X-ray diffraction, X-ray fluorescence and scanning electron microscopy. The obtained samples are cubic phase KTN nanocrystallines with high-purity and well-crystallized. The grain size of Fe doped KTN increases and the lattice parameters change slightly. Moreover, the particle separation becomes to be better and the particle distribution becomes more homogeneous after Fe-doping. The Fe-doping content is better to be controlled under 1.8 mol% to prevent impurities.